COMMUNICATION – ORIENTED LEARNING AS ONE OF THE EFFECTIVE METHODS OF TEACHING A FOREIGHN LANGUAGE - Dzhumagulova, S. K. (Наука и образование №4, 2020)
The article discusses the topical issues related to the analysis of modern domestic and foreign methods of teaching a foreign language in the higher education system. Also, this article highlights the communication-oriented methods and their role in the education of the creative personality of students in modern conditions. Such strategic provisions, characteristic of communicative teaching to communicate in a foreign language, are taken into account, such as: communicative orientation of teaching all types of speech activity and language means, stimulating students' speech and thinking activity, individualization of teaching, situational organization of the learning process, novelty and in formativeness of educational material, the formation of communicative competence. Communication-oriented teaching of a foreign language is an effective method that allows a student to master a foreign language by the end of their studies at a level sufficient for adaptation in a foreign language society.
Keywords: научный журнал; отечественное издание; периодическое издание; английский язык; языкознание; иностранный язык; коммуникативно-ориентированное обучение; methods of teaching a foreign language; communication-oriented methods